DESCRIPTION OF MACRONUTRIENT INTAKE AND NUTRITIONAL STATUS IN PATIENTS WITH TUBERCULOSIS IN THE OUTPATIENT ROOM OF PROF. DR. DR. W. Z. JOHANNES KUPANG - Boro, Regina Maria; Adi, Anak Agung Ayu Mirah (Kupang Journal of Food and Nutrition Research, 2024)
Tuberculosis is still a global health problem. According to the East Nusa Tenggara Provincial Health Office (NTT Provincial Health Office), the number of new cases of smear-positive pulmonary TB in 2017 was 29%. Based on data from the medical records of Prof.DR W.Z Johannes Kupang Hospital, 51 patients with tuberculosis who underwent outpatient treatment in the last 3 months. The purpose of this research to know the description of intake of macronutrients and nutritional status in TB patients in the outpatient room of Prof. Hospital. Dr. W Z Johannes Kupang. This type of observational research with a descriptive design was carried out in January 2023. Sampling used the Accidental Sampling technique, which consisted of 34 TB respondents. The data taken includes intake of macronutrients and nutritional status (secondary). The results showed that of the 34 respondents with TB, the energy intake of the respondents was mostly in the category of severe deficit (61.8%), the highest percentage of respondents' protein intake was in the category of moderate deficit (38.2%), the fat intake of the respondents was mostly in the category of severe deficit (67.6%), most of the respondents' carbohydrate intake was in the category of severe deficit (79.4%) and the highest percentage of patients' nutritional status was in the underweight category (29.4%). Overview of macronutrient intake and nutritional status in TB patients in the outpatient room of Prof. Dr. Most of W Z Johannes Kupang are in the category of weight deficit and underweight nutritional status.